2015
DOI: 10.1038/srep08820
|View full text |Cite
|
Sign up to set email alerts
|

Variations of gastric corpus microbiota are associated with early esophageal squamous cell carcinoma and squamous dysplasia

Abstract: Observational studies revealed a relationship between changes in gastric mucosa and risk of esophageal squamous cell carcinoma (ESCC) which suggested a possible role for gastric microbiota in ESCC carcinogenesis. In this study we aimed to compare pattern of gastric corpus microbiota in ESCC with normal esophagus. Cases were included subjects with early ESCC (stage I–II) and esophageal squamous dysplasia (ESD) as the cancer precursor. Control groups included age and sex-matched subjects with mid-esophagus esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 44 publications
0
61
0
Order By: Relevance
“…While it is generally accepted that gastro‐oesophageal reflux modifies the oesophageal microbiota, a recent study showed that this influence could be bidirectional since gastric bacteria differed between patients with normal oesophageal tissue and those with oesophagitis or BE . Gastric microbiota changes have also been associated with oesophageal cancer as higher abundance of Clostridiales and Erysipelotrichales order members were found in the gastric microbiota of early squamous dysplasia and oesophageal squamous cell cancer …”
Section: Resultsmentioning
confidence: 99%
“…While it is generally accepted that gastro‐oesophageal reflux modifies the oesophageal microbiota, a recent study showed that this influence could be bidirectional since gastric bacteria differed between patients with normal oesophageal tissue and those with oesophagitis or BE . Gastric microbiota changes have also been associated with oesophageal cancer as higher abundance of Clostridiales and Erysipelotrichales order members were found in the gastric microbiota of early squamous dysplasia and oesophageal squamous cell cancer …”
Section: Resultsmentioning
confidence: 99%
“…Concerning ESCC, a negative correlation between esophageal microbial richness and esophageal squamous dysplasia (ESD) has recently been observed using a culture‐independent approach, suggesting that individuals with a lower esophageal microbial complexity could be more prone to develop ESD. An additional study performed using an NGS approach demonstrated an enrichment in Clostridiales and Erysipelotrichales (phylum Firmicutes) in the gastric corpus microbiota of patients affected by ESD and ESCC compared with controls, pointing to a possible involvement of gastric dysbiosis in ESD–ESCC progression . Recently, a possible role for specific bacteria in the pathogenesis of ESCC has also been investigated by Gao et al ., who focused on the possible relationships between Porphyromonas gingivalis , an oral pathogen thought to be involved in oral squamous cell carcinoma tumorigenesis, and ESCC, given the histological similarity of the two cancers.…”
Section: The Microbiota In Diseased Esophagus and Its Potential Role mentioning
confidence: 99%
“…They suggested that individuals with lower esophageal microbial complexity are more prone to developing esophageal squamous dysplasia 60. Another study using 16S rDNA sequencing technology demonstrated that, relative to controls, the gastric corpus microbiota of patients affected by esophageal squamous dysplasia and esophageal squamous cell carcinoma are enriched in Clostridiales and Erysipelotrichales, suggesting that gastric dysbiosis is involved in the progression from esophageal squamous dysplasia to squamous cell carcinoma 61. Gao et al 62.…”
Section: Microbiome and Esophageal Squamous Cell Carcinomamentioning
confidence: 99%